DESCRIPTIONS OF THE CONSIDERED REASON BY THE FUNDAMENTALISTS - Atheer Awwad Jamal Abd Al-Fattah Al-Jumaili (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The study aimed to explain the importance of the reason on which the Islamic laws aremeasuredand how are the descriptions considered. Also, showing the importance of knowledge to the responsible person who performs the duties in Islamabout these descriptions. The descriptions were mentioned through the fundamentalists without detailing them for each section. Thus, I extrapolated the mention of these descriptions, count them, and mention the considered descriptions without the canceled because the invalid is the one that I did not mention in the subject matter, and to clarify the topic and detail its merits, I studied the subject thoroughly and extensively and it is well-known to the fundamentalists.The difference in its parts and divisions, and I showed in my research the most important issues related to the cause and its descriptions. I also presented the combined and the different and also the differentiated rulings and issues in the jurisprudential branches in applications for the various issues mentioned in my topic.